On the variability of the Caribbean lowlevel jet during winter: revisited - Maldonado Mora, Tito José; Rutgersson, Anna; Amador Astúa, Jorge Alberto; Alfaro Martínez, Eric J.; Claremar, Björn (Memorias de la European Geosciences Union General Assembly 2014, 2014)
póster -- Universidad de Costa Rica. Centro de Investigaciones Geofísicas, 2014 The Caribbean low-level jet (CLLJ) is a strong wind current over the Caribbean Sea. Annually it has two peak periods, where February and July being the winter and summer components, respectively. The CLLJ is an important element for the climate and weather of the region, due, in part, to its interaction with the convective activity over the Caribbean, mainly during the second half of the year. Nevertheless, there still is little knowledge about its variability and the relationship with fluctuations of the large-scale fields such as the sea surface temperatures (SST) and the sea level pressure (SLP). Therefore, this study seeks to establish a statistical relationship between the changes in the intensity of the jet with the anomalies of SST and SLP. Furthermore, the relationship with large-scale variability modes such as El Niño, the North Atlantic Oscillation (NAO) among others, during the jet maxima, is analyzed. Wind products of the NCEP/NCAR reanalysis, and SSTs from NOAA are used for the base period 1950-2010. A CLLJ index describing the variability of the wind at 925 hPa is defined for the region bounded by 12.5 – 17.5 N and 80 – 70 W. Preliminary results show that the correlation patterns of the wind index with the SST anomalies remain similar in both seasons over the Atlantic and the Caribbean Sea, while a more complex distribution is observed over the Pacific in each season. The latter evidences different feedback mechanisms during each month in the Pacific. In February warm (cold) waters in the eastern tropical Pacific would decrease (increase) the easterlies intensity during winter. The opposite is observed during July. Moreover, the correlation of the wind index with the anomalies of SLP exhibits different behavior during both month as well. During the winter peak the jet reacts to the location and intensity of the subtropical highs in the North Pacific and Atlantic. It also shows a negative association with the SLP ...